ASSESSMENT OF KNOWLEDGE & PRACTICE OF CONTRACEPTIVES IN FEMALES OF REPRODUCTIVE AGE GROUP AT A TERTIARY CARE HOSPITAL: Knowledge & Practice of Contraceptives - Babar, Nabeela Fazal; Ahmed, Mahmood; Khan, Mohammad Babar; Khan, Mohammad Wasif (Pakistan Armed Forces Medical Journal, 2009)
Objectives: To assess the knowledge & practice of contraceptives in females of reproductive age group.Study Design: Cross sectional descriptive.Place and Duration of Study: OPD of Fauji Foundation Hospital from February 2008 – September 2008.Subjects and Method: 339 Females of age b/w of 15 – 49 years attending OPD of Fauji Foundation Hospital were included in study. A structured questionnaire was used to collect data.Results: Eighty eight percent of the females in our study sample were familiar with one or more methods of contraception (72.7%were familiar with combined oral contraceptive pill (COCP), 60.7% were aware of intra uterine contraceptive device (IUCD) &76% knew about condoms) whereas 12% showed ignorance. 64.6% of the study population was contraceptive users & 35.4% were not using any method of contraception. Regarding preferred method of contraception 34.6% of females said they are using COCP, about 21.8% females said their tubes had been liagated whereas 26.9%& 16.7% were using IUCD & Condoms respectively. Almost 46%of our study population said that contraceptive method they were using was suggested by their husbands, 44 % said by health professional .Only 10 % of the study population were using a method of their own choice.Conclusion: The present study concludes that there is a gap between knowledge (88%) and use (64.6%) of contraceptives among females of reproductive age group. Another important inference drawn from the study is that men should be made equal targets of such programs in Pakistan since 46% females in our study population were using method of contraceptive suggested by their husband.